TRADISI KAWIN TANGKAP DI TINJAU DARI PERSPEKTIF HUKUM ISLAM - Dedi Indrama (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2022)
This study was conducted to find out more about capture marriages whether the marriage is legal or not, because marriage is not something that can be played with. We also have to look at the law, the validity of the marriage and the provisions that the couple will bring to their future. Do not let the marriage lead to divorce and divorce in a time that is still as old as corn.In this research, the researcher dissects books from several sources to see how the process until marriage occurs so that we can study together in the future. The author takes samples from several regions that still carry out this tradition until now. From several areas taken, there are still many marriages that are religiously illegal, but the couple is still carrying on the relationship.